Hubungan Asupan Vitamin C, Karbohidrat, Status Gizi dan Aktivitas Fisik terhadap Kadar Gula Darah Penderita Diabetes Melitus Tipe 2 - Febry Yohandrey; Kasmiyetti Kasmiyetti; Hasneli Hasneli (Jurnal Sehat Mandiri, 2025)
Diabetes mellitus (DM) is a metabolic disorder of carbohydrates, lipids, and proteins characterized by hyperglycemia. Risk factors include unbalanced diet, nutritional status, and physical activity. According to the Padang City Health Profile at the Andalas Health Center, 69% of patients are people with DM. This study aimed to examine the association between vitamin C intake, carbohydrate intake, nutritional status, and physical activity with blood sugar levels among patients with type 2 DM. This research employed a cross-sectional design and Chi-Square analysis. A total of 52 participants were selected using accidental sampling. Primary data included vitamin C and carbohydrate intake (SQ-FFQ and 2x24-hour food recall), nutritional status (BMI), and physical activity (interview). The results showed significant associations between carbohydrate intake and nutritional status with blood sugar levels, while vitamin C intake and physical activity were not significantly associated. Regulating carbohydrate intake and maintaining good nutritional status are important to help control blood sugar levels. Nutrition education and regular monitoring are recommended to prevent complications and improve patients’ quality of life.